Strategic climate change litigation: a catalyst for the evolution of the principles of environmental law in Brazil - Ana Maria; Monteiro Martinez, Matheus (Revista de Derecho Ambiental, 2024)
In view of the need to halt the increase in global temperature in the range of 1.5ºC by the end of the century, strategic climate change litigation emerges as an instrument to fight climate change. On the other hand, due to Brazil’s civil law legal system nature, interpretation arises as the technique responsible for updating law and its principles when it no longer corresponds to the demands of reality. Thus, this article seeks to defend strategic climate change litigation also as “catalyst” – an instrument capable of accelerating the environmental law principles interpretation’s evolutionary process. For this purpose, a sample of Brazilian cases was selected upon the information available in climate change litigation databases until April 2023. As analysis results, it was possible to project two scenarios of innovative interpretation proposals, one concerning new ways in which some principles were interpreted, such as the progressive nature of climate protection instilled in the non-regression principle, and the other regarding the presentation of truly unprecedented proposals, such as i) the principle of protection of the integrity of the climate system; ii) the constitutional and supra-legal duty of climate protection based on the understanding of international climate treaties as human rights treaties, and iii) the constitutional environmental subsystem.